Chemical characterization of Pleurotus eryngii polysaccharide and its tumor-inhibitory effects against human hepatoblastoma HepG-2 cells. (15th March 2016) - Ren, Daoyuan; Wang, Ning; Guo, Jianjun; Yuan, Li; Yang, Xingbin
Graphical abstract: Highlights: PEP is the crude heteropolysaccharides isolated from Pleurotus eryngii . PEP-1 and PEP-2 were purified from PEP by Cellulos e DEAE-52 and Sephadex G-100. High molecular mass PEP-2 exhibits more potent anticancer effect than PEP-1. ROS was a critical mediator in PEP-2 induced HepG-2 cellular apoptosis. PEP-2 is a good candidate for dietary supplement and therapeutic application in cancer. Abstract: This study was designed to investigate the chemical characterization and antitumor effects of Pleurotus eryngii polysaccharides (PEP). The crude PEP was fractionated into two fractions, namely PEP-1 and PEP-2. HPLC analysis showed that PEP-1 and PEP-2 were heteropolysaccharides mainly composed of glucose with the average molecular weights of 2.54 × 10 4  Da (PEP-1) and 4.63 × 10 5  Da (PEP-2), respectively. High molecular mass PEP-2 was shown to exhibit stronger growth inhibition against human hepatoblastoma HepG-2 cells in comparison with PEP-1. Flow cytometric analysis showed that PEP-2 exerted a stimulatory effect on apoptosis of HepG-2 cells, and induced the cell-cycle arrest at the S-phase, with the observation of intracellular ROS production. These findings suggest that the polysaccharides, especially PEP-2, are very important nutritional ingredients responsible for the anticancer health benefits of P. eryngii .